2020
DOI: 10.3390/su12030950
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Mental Health of Older Adults in China

Abstract: In this paper, we explore the association between air pollution and the mental health and depression of older adults in China. Along with the rapid economic development, concerns about air pollution and recognition of the importance of mental health have risen remarkably in China. Although no firm evidence of an association between air pollution and overall mental health has been found, the results show significant evidence of a positive relationship between air pollution and depression. Moreover, we observe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…The steps required include the following: (1) The support of laws and regulations on air pollution control by referring to, to name some, ambient air quality standard regulations according to WHO standards, regulations on the use of vehicle fuel, regulations on motor vehicle emission testing, and regulations to reduce air pollution emissions from industry; (2) better cross-sectoral coordination with academics and professional organizations to address air pollution problems across all sectors, using studies to determine the sources of air pollution in urban areas (emissions inventory) and to assess the health impact of air pollution on communities and efforts; (3) taking steps to reduce air pollution such as promoting and implementing emission tests for motor vehicles entering the Urip Sumoharjo-Perintis Kemerdekaan road corridor, especially public vehicles or freight vehicles, and monitoring air pollution emissions and administering strict punishments to industries that are not environmentally friendly; (4) promoting alternative power plants, such as wind power, wave power, and solar power, to reduce air pollution emissions from power plants; (5) supporting mass transportation facilities that are safe, comfortable, inexpensive, environmentally friendly, and easily accessible; (6) preparing parking lots adjacent to public transportation facilities that are feasible, safe, affordable, and able to accommodate needs for transportation for economic activities and other social activities; (7) campaigning for the use of electric vehicles (cars and electric motorbikes) and increasing the number of public vehicles with electric power; (8) increased tree planting and green areas; (9) maximizing air pollution monitoring and early warnings in the community by increasing the number of monitoring points/measuring instruments for air quality and by providing information that is easily accessible to the public; (10) regularly providing information to the public about unhealthy air quality conditions and the anticipatory steps that can be taken by the public in various media (print, electronic, and social media); and (11) preparing a health service system to serve people affected by air pollution. Although no firm evidence of an association between air pollution and overall mental health has been found, the results show significant evidence of a positive relationship between air pollution and depression [121,122].…”
Section: Environmental Management and Air Pollution Control Solutionscontrasting
confidence: 78%
“…The steps required include the following: (1) The support of laws and regulations on air pollution control by referring to, to name some, ambient air quality standard regulations according to WHO standards, regulations on the use of vehicle fuel, regulations on motor vehicle emission testing, and regulations to reduce air pollution emissions from industry; (2) better cross-sectoral coordination with academics and professional organizations to address air pollution problems across all sectors, using studies to determine the sources of air pollution in urban areas (emissions inventory) and to assess the health impact of air pollution on communities and efforts; (3) taking steps to reduce air pollution such as promoting and implementing emission tests for motor vehicles entering the Urip Sumoharjo-Perintis Kemerdekaan road corridor, especially public vehicles or freight vehicles, and monitoring air pollution emissions and administering strict punishments to industries that are not environmentally friendly; (4) promoting alternative power plants, such as wind power, wave power, and solar power, to reduce air pollution emissions from power plants; (5) supporting mass transportation facilities that are safe, comfortable, inexpensive, environmentally friendly, and easily accessible; (6) preparing parking lots adjacent to public transportation facilities that are feasible, safe, affordable, and able to accommodate needs for transportation for economic activities and other social activities; (7) campaigning for the use of electric vehicles (cars and electric motorbikes) and increasing the number of public vehicles with electric power; (8) increased tree planting and green areas; (9) maximizing air pollution monitoring and early warnings in the community by increasing the number of monitoring points/measuring instruments for air quality and by providing information that is easily accessible to the public; (10) regularly providing information to the public about unhealthy air quality conditions and the anticipatory steps that can be taken by the public in various media (print, electronic, and social media); and (11) preparing a health service system to serve people affected by air pollution. Although no firm evidence of an association between air pollution and overall mental health has been found, the results show significant evidence of a positive relationship between air pollution and depression [121,122].…”
Section: Environmental Management and Air Pollution Control Solutionscontrasting
confidence: 78%
“…A large body of literature has focused on the health effects of the physical and social neighborhood environment. Scholars have found that the physical neighborhood environment such as the noises and environmental pollution around residences can reduce residents' self-rated physical and mental health [11][12][13][14][15], while sound public facilities and complete medical services can make residents engage in more physical exercise and get easier access to medical assistance, further lowering the incidence of chronic diseases and improving their self-rated physical and mental health [16][17][18][19][20][21][22]. The influence of the social neighborhood environment on residents' health has also drawn certain research attentions.…”
Section: Introductionmentioning
confidence: 99%
“…While smoke, and heat to a lesser extent, were less immediately life-threatening in Canberra, the event fulfills the definition of a disaster as a “basic disruption of social context within which individuals and groups function” [( 53 ), p. 651 cited in ( 25 )]. It shared similarities with man-made air pollution in other countries ( 54 , 55 ) and with drought which produces an increased risk of poorer physical and mental health ( 56 ) but less obvious threat to mortality.…”
Section: Discussionmentioning
confidence: 96%